Peran Majelis Taklim dalam Membangun Harmoni Masyarakat Multikultural di Desa Sungai Kunyit - Sofyan, Anas; Hasan, Munawir; Mahrus, Erwin (Kartika: Jurnal Studi Keislaman, 2025)
Sungai Kunyit Village, rich in ethnic and cultural diversity, has received little attention regarding the role of majelis taklim as a space for community development. In such a diverse society, religious learning forums that can bridge differences and strengthen social cohesion are crucial. This study employs a descriptive qualitative approach to explore the role of Islamic studies in fostering a harmonious multicultural life in Sungai Kunyit Village, Mempawah Regency, West Kalimantan. The research was conducted from January to March 2025 and focuses on religious activities carried out in a majelis taklim that regularly holds Islamic study sessions and social programs. Data collection techniques included observation, in-depth interviews, and documentation. Data were analyzed using the interactive model developed by Miles and Huberman. The main findings reveal that the majelis taklim not only functions as a center for religious development but also serves as an effective platform for social dialogue and education in promoting the values of tolerance, solidarity, and respect for diversity. The moderate and contextual preaching of Ustaz successfully fostered a collective awareness among participants of the importance of living peacefully amidst ethnic and religious differences. The majelis taklim proved to be a medium for strengthening social cohesion through inclusive interactions between different groups, including non-Muslim residents. The results of this study suggest that majelis taklim holds significant potential as a strategic partner in promoting religious moderation, especially in areas characterized by high levels of social and cultural diversity. Therefore, policy support from both the government and religious institutions is essential to empower majelis taklim to play a greater role in building an inclusive and peaceful society.